TikTok's role in re-popularizing ‘Happy House’ songs: A netnographic study - Barbara, Virda Kurnia; Achmad, Zainal Abidin (Indonesian Journal of Social Sciences, 2025)
This study examines how the song ‘Happy House’ by Siouxsie and the Banshees experienced a resurgence and spread on TikTok, highlighting the importance of understanding how old songs become relevant in the digital age. This study highlights TikTok’s features and user engagement as key levers in this process. The researchers used qualitative methods through a netnography approach to explore the cultural factors that drove the song’s success, including TikTok’s algorithm, user engagement, and content production processes. The researchers analyzed user engagement, comments, and viral content trends to uncover how the platform facilitated the song’s resurgence. The findings identified three key components that drove the song’s popularity: TikTok’s app features, viral trends, and user-generated content, including remixes and covers. These factors provide the possibility for older songs to effectively connect with younger audiences. In addition, the song’s lyrics and themes resonate emotionally with contemporary narratives, which further enhances its appeal. The study concludes that TikTok plays an active role in shaping music consumption needs. By allowing genres of the past to resonate with modern audiences, TikTok preserves and revives musical heritage. This process fosters intergenerational connections through shared cultural expression, highlighting the platform’s power in the digital landscape.